Large Dark Matter Content and Steep Metallicity Profile Predicted for Ultradiffuse Galaxies Formed in High-spin Halos - Benavides Blanco, Jose Antonio (2024)
We study the stellar properties of a sample of simulated ultradiffuse galaxies (UDGs) with stellar mass M⋆ = 107.5–109M⊙, selected from the TNG50 simulation, where UDGs form mainly in high-spin dwarf-mass halos. We divide our sample into star-forming and quenched UDGs, finding good agreement with the stellar assembly history measured in observations. Star-forming UDGs and quenched UDGs with M⋆ ≥ 108M⊙ in our sample are particularly inefficient at forming stars, having 2–10 times less stellar mass than non-UDGs for the same virial mass halo. These results are consistent with recent mass inferences in UDG samples and suggest that the most inefficient UDGs arise from a late assembly of the dark matter mass followed by a stellar growth that is comparatively slower (for star-forming UDGs) or that was interrupted due to environmental removal of the gas (for quenched UDGs). Regardless of efficiency, UDGs are 60% poorer in [Fe/H] than the population of non-UDGs at a fixed stellar mass, with the most extreme objects having metal content consistent with the simulated mass–metallicity relation at z ∼ 2. Quenched UDGs stop their star formation in shorter timescales than non-UDGs of similar mass and are, as a consequence, alpha enhanced with respect to non-UDGs. We identify metallicity profiles in UDGs as a potential avenue to distinguish between different formation paths for these galaxies, where gentle formation as a result of high-spin halos would present well-defined declining metallicity radial profiles while powerful-outflows or tidal stripping formation models would lead to flatter or constant metallicity as a function of radius due to the inherent mixing of stellar orbits.